G-quadruplexes originating from evolutionary conserved L1 elements interfere with neuronal gene expression in Alzheimer’s disease - Roy Hanna (Nature Portfolio, 2021)
G-quadruplexes (G4) can be formed from DNA sequences containing consecutive guanines organized in 4-interspaced tandem repeats. Here the authors reveal the association between G4 structures present at specific loci in Alzheimer’s disease neurons and reduced gene expression and perturbed alternative splicing.